SUSTAINABLE CULTURAL DEVELOPMENT: THE FATE OF BALINESE ADAT VILLAGE POSTERIOR THE ENACTMENT OF LAW NUMBER 6 YEAR 2014 CONCERNING VILLAGE - I Nyoman Nurjaya (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2015)
Pengakuan keberadaan masyarakat adat sangat tergantung pada kehendak pemerintah yang berkuasa. Pemerintah Desa sebagaimana dirumuskan dalam Undang-Undang Nomor 6 Tahun 2014 tentang Desa serta Peraturan Pemerintah Nomor 43 Tahun 2014 tentang Peraturan Pelaksanaan Undang-Undang Nomor 6 Tahun 2014 telah secara alami menjadi hukum birokrasi dan pejabat bahwa desa diatur dalam sistem pemerintah daerah di bawah pengawasan hukum negara. Dalam kasus Bali dan pemerintah daerah Bali, terdapat konsekuensi hukum dengan nasib dan masa depan keberadaan dan kehidupan desa adat/desa pakraman sebagai sistem sosial dan budaya masyarakat Hindu, yaitu hukum berdasarkan dari pakraman pembangunan desa adat/desa tidak akan tetap menjadi awig-awig sebagai hukum adat masyarakat tradisional Bali; filsafat dan esensi, fungsi dan peran desa adat/desa pakraman berubah secara fisik serta mengakhiri dan hilangnya komunitas kehidupan masyarakat Bali; adat tradisional dan sistem pemerintahan harus berubah sesuai dengan sistem pemerintahan desa dinas (Kelurahan); di satu desa sisi adat/desa pakraman harus mengatur urusan administrasi dan birokrasi di bawah struktur pemerintah daerah, dan di sisi lain desa adat adalah pada saat yang sama yang bertanggungjawab untuk mengatur dan bertanggungjawab tentang budaya, tradisi dan ritual adat serta sebagai urusan agama Hindu, pemandangan desa pakraman adat/desa harus benar-benar diabaikan dalam kehidupan sehari-hari desa Bali dan masyarakat.The recognition of indigenous peoples existence is very dependent on the will of the Government. The village government as formulated in Act number 6/2014 of the village, as well as Government Regulation number 43/2014 about Implementation of the Act number 6/2014 has naturally become a bureaucratic and legal officials law, that the village is set in the system of local government under the supervision of State law. In the case of Bali and the local Government of Bali, there is legal consequences with the fate and the future existence and life of indigenous village/pakraman village as a social and cultural system of the Hindu society, it is the law on the development basis of the indigenous village/pakraman village will not remain be ”the awig-awig” as Balinese traditional society customary law; philosophy and the essence, function and role of the indigenous village/pakraman village changed physically as well as community life of Balinese people loss; traditional customs and Government system should be changed in accordance with the system of the village Government; on one side the customs affairs village should organize pakraman village administration and bureaucracy under the structure of local governments, and on the other hand the indigenous village is at the same time responsible to organize and responsible about the culture, traditions, customs and ritual as Hindu affairs, village understanding of pakraman village customs and traditions should be completely ignored in Balinese village daily community life.